Somalia and the Democratic Republic of Congo Join the East African Community: What Next for the Common Market? - Ntara, Caroline (HAPSc Policy Briefs Series, 2024)
The growing number of member states in the East African Community (EAC) calls for greater efforts in common market integration. The region has been facing constraints in the execution of its Common Market Protocol (CMP) established in 2010 to sanction the uninhibited movement of capital, workers, people, products, and services and permit the right of establishment and inhabitation. There are deterrents ranging from insecurity, the absence of common market laws, financial constraints, failure to observe the principle of subsidiarity, limited recognition and facilitation of the informal sector, poor regional connectivity and challenges in the identification of persons, that must be subdued. With the new entrants, these challenges can become more pronounced and stall the regional integration agenda. However, the prospects that the entrants bring to the EAC including new markets, immense resources and thriving youthful populations can be tapped into for the benefit of the region. This paper provides policy recommendations on how the EAC can accommodate new members and profit from a robust common market.